Flujos óptimos de potencia reactiva basado en óptimo despacho de carga usando GAMS. - Romero Ramos, Israel Jacobo (2017)
In this paper, it is proposed, modeled and solved the power flow problem with the objective of reassigning the reagents flow in a Power Electrical System (PES), in order to minimize its losses and to evaluate its advantages. For this purpose the parameters of generators, bars, lines and loads of the case of 14 bars of DigSilent Power Factory were used, being considered similar to the SEP model, being used for pertinent analyzes. The aim of this work is to minimize reactive power losses, using the nonlinear programming models (NPL) through the GAMS software, and applying the MINOS as solver, which uses the reduced gradient method for linear constraints and nonlinear function objective, and also for problems with nonlinear constraints, it is used the lagrangian increased algorithm. Once the results of the optimization with GAMS were obtained , it will be analyzed them and compared with the results of the simulation case of 14 bars, in order to obtain conclutions about the benefit of solving an optimal power flow problem, focused on the minimization of reactive power in a system. Keywords: Active Power, Electrical